Physical rehabilitation interventions for adult patients during critical illness: an overview of systematic reviews. Issue 10 (24th May 2016) - Connolly, Bronwen; O'Neill, Brenda; Salisbury, Lisa; Blackwood, Bronagh
Abstract : Background: Physical rehabilitation interventions aim to ameliorate the effects of critical illness-associated muscle dysfunction in survivors. We conducted an overview of systematic reviews (SR) evaluating the effect of these interventions across the continuum of recovery. Methods: Six electronic databases (Cochrane Library, CENTRAL, DARE, Medline, Embase, and Cinahl) were searched. Two review authors independently screened articles for eligibility and conducted data extraction and quality appraisal. Reporting quality was assessed and the Grading of Recommendations Assessment, Development and Evaluation approach applied to summarise overall quality of evidence. Results: Five eligible SR were included in this overview, of which three included meta-analyses. Reporting quality of the reviews was judged as medium to high. Two reviews reported moderate-to-high quality evidence of the beneficial effects of physical therapy commencing during intensive care unit (ICU) admission in improving critical illness polyneuropathy/myopathy, quality of life, mortality and healthcare utilisation. These interventions included early mobilisation, cycle ergometry and electrical muscle stimulation. Two reviews reported very low to low quality evidence of the beneficial effects of electrical muscle stimulation delivered in the ICU for improving muscle strength, muscle structure and critical illness polyneuropathy/myopathy. One review reported that due to a lack of good quality randomised controlled trials and inconsistency in measuring outcomes, there was insufficient evidence to support beneficial effects from physical rehabilitation delivered post-ICU discharge. Conclusions: Patients derive short-term benefits from physical rehabilitation delivered during ICU admission. Further robust trials of electrical muscle stimulation in the ICU and rehabilitation delivered following ICU discharge are needed to determine the long-term impact on patient care. This overview provides recommendations for design of future interventional trials and SR. Trial registration number: CRD42015001068.